An Unusual Presentation of Glandular Fever - Dominic Worku; Li Hui Chang; Ian Blyth (Case Reports in Infectious Diseases)
Epstein-Barr virus (EBV) is an ubiquitous DNA herpesvirus with >90% of adults >40 years of age showing a serological response. While in their youth, primary EBV infection may pass unnoticed, young adults have a high incidence of infectious mononucleosis (IM). This is characterized by a triad of pharyngitis, cervical lymphadenopathy, and fever because of a self-limiting lymphoproliferative disease. Common complications include but are not limited to hepatitis, splenomegaly, encephalitis, and haemophagocytic lymphohistiocytosis (HLH) with evidence that Caucasian males and smokers are more likely to suffer severe disease. Here we present a 21-year-old male who presented with a 2-week history of fever, dry cough, and a 4-week history of pharyngitis. He had no exposure to unwell contacts and denied any new sexual partners. Examination revealed general pallor with tender bilateral cervical lymphadenopathy and pharyngeal erythema. Admission bloods revealed pancytopenia (WCC 1.5 × 109/L, Plt 84 × 109/L, and Hb 82 g/L) with normal reticulocyte count and raised mean corpuscular volume (114 fL). Serum vitamin B12 and folate were low with serum ferritin raised (1027 µg/L) suggesting a proinflammatory state. Admission liver function tests, coeliac serology, autoimmune panel (ANA, ANCA, and anti-dsDNA), hepatitic (hepatitis A, B, and E), human immunodeficiency virus (HIV), toxoplasmosis, parvovirus, and CMV serology were normal. The monospot test on day 1 of the presentation was negative. Ultrasound (US) of the abdomen on day 3 of the presentation revealed isolated splenomegaly (16.8 cm). Day 4 EBV serology (VCA IgM, VCA IgG, and EBNA IgG) was negative as such haematological investigations including JAK2, serum free light chains, and BCR-ABL were undertaken alongside cervical lymph node core biopsy. Repeat Monospot testing on day 7 came back positive. Repeat EBV serology now showed equivocal EBV VCA IgG (0.77 OD) and positive VCA IgM (9.04 OD) with concurrent new hepatitis. Histopathology of the core biopsy revealed Sternberg-reed cells and a mixed immunoblastic reaction in keeping with resolving IM. This case highlights the need for physicians to have a strong clinical suspicion of IM and understand the multiple ways in which IM may be present as well as the time lag to positivity in serological testing.